2017
DOI: 10.1186/s12969-017-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided steroid tendon sheath injections in juvenile idiopathic arthritis: a 10-year single-center retrospective study

Abstract: BackgroundThe aims of this study were to: (a) Identify tendon sheaths most commonly treated with steroid injections in a pediatric patient population with Juvenile Idiopathic Arthritis (JIA); (b) Describe technical aspects of the procedure; (c) Characterize sonographic appearance of tenosynovitis in JIA; (d) Assess agreement between clinical request and sites injected.MethodsThis was a 10 year single-center retrospective study (May 2006-April 2016) of patients with JIA referred by Rheumatology for ultrasound-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…We included examination of the ATC in our US procedures and in our data analysis, but we found that tenosynovitis was less frequent in this compartment than in the MTC and LTC. This finding is in keeping with the notion that the use of US to guide tendon sheath injections in JIA is more common in the MTC and LTC of the ankle (31). The observation that the clinician did not report involvement of the ATC in any ankles in our patients may be explained, at least in part, by considering the fact that tenosynovitis affecting the ATC may easily mimic the presence of synovitis in the anterior joint structures of the ankle, particularly in the TT joint and IT joint, since this tendon compartment runs superficially above the anterior surface of the ankle region.…”
Section: Discussionsupporting
confidence: 87%
“…We included examination of the ATC in our US procedures and in our data analysis, but we found that tenosynovitis was less frequent in this compartment than in the MTC and LTC. This finding is in keeping with the notion that the use of US to guide tendon sheath injections in JIA is more common in the MTC and LTC of the ankle (31). The observation that the clinician did not report involvement of the ATC in any ankles in our patients may be explained, at least in part, by considering the fact that tenosynovitis affecting the ATC may easily mimic the presence of synovitis in the anterior joint structures of the ankle, particularly in the TT joint and IT joint, since this tendon compartment runs superficially above the anterior surface of the ankle region.…”
Section: Discussionsupporting
confidence: 87%
“…A 1.5-inch needle was visualized in the long axis of the transducer and, with US control, was advanced. Once the needle tip was seen within the peritendinous effusion, the effusion was aspirated and collected for further analysis as described in Wu et al [ 24 ], Chiodo et al [ 25 ], and Peters et al [ 26 ]. HA was injected into the peritendinous area using real-time US monitoring (T0).…”
Section: Methodsmentioning
confidence: 99%
“…This technique offers greater clinical efficacy by ensuring the correct injection of the therapeutic substance and thus reducing the risk of complications. In clinical practice, the most commonly injected tendon sheaths seem to be the tibialis posterior, peroneus longus and peroneus brevis, as reported in a recent observational study [48]. No major complications were observed [48].…”
Section: Pathological Us Findings In Patients With Different Rheumatomentioning
confidence: 86%
“…MSUS in monitoring the disease activity and response to treatment MSUS imaging can also play a key role in guiding steroid injections into joints, tendon sheathsand even tendon insertions (entheses) [46][47][48]. Local corticosteroid (preferably triamcinolone hexacetonide) injections are a common treatment for young patients with JIA, well tolerated and effective for several months, used particularly in the oligoarthritis subset of JIA.…”
Section: Pathological Us Findings In Patients With Different Rheumatomentioning
confidence: 99%